MENINGKATKAN KINERJA: INTERNAL & EXTERNAL FACTORS - Ade Suherlan (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
Providing excellent service is mandatory, the customer feels the warmth of the employee, hospitality, smile, responsiveness, and tenderness. The company must work hard, encourage performance improvement, commitment, stimulate self-enthusiasm by promoting career development. This research is intended to look at internal and external performance factors. The reason for using quantitative methods is simple, and can show clarity of interpretation. To collect data, questionnaires were distributed. Respondents answered according to predetermined criteria (Likert scale), then the data were analyzed using regression. The results of the study confirm that performance can develop significantly if internal and external factors are built up. In the long term career strategies are needed, but in operational (daily) efficacy and commitment are needed